Remnants and changes in facial emotion processing in women with remitted borderline personality disorder: an EEG study - Schneider, Isabella; Bertsch, Katja; Izurieta Hidalgo, Natalie A.; Müller, Laura Elisa; Schmahl, Christian; Herpertz, Sabine (European archives of psychiatry and clinical neuroscience, 2018)
According to longitudinal studies, most individuals with borderline personality disorder (BPD) achieve remission. Since BPD is characterized by disturbed emotion recognition, this study investigated behavioral and electrophysiological correlates of facial emotion classification and processing in remitted BPD. 32 women with remitted BPD (rBPD), 32 women with current BPD (cBPD), and 28 healthy women (HC) participated in an emotion classification paradigm comprising blends of angry and happy faces while behavioral and electroencephalographic (event-related potentials) data were recorded. rBPD demonstrated a convergence in behavior towards HC in terms of responses and reaction times. They evaluated maximally ambiguous faces more positively and exhibited faster reaction times when classifying predominantly happy faces compared to cBPD. Group × facial emotion interaction effects were found in early electrophysiological processes with post hoc tests indicating differences between rBPD and cBPD but not between rBPD and HC. However, BPD-like impairments were still found in rBPD in later processing (P300). Our results suggest a reduction in negativity bias in rBPD on the behavioral level and a normalization of earlier stages of facial processing on the neural level, while alterations in later, more cognitive processing do not remit. Early processing may be more state-like, while later impairments may be more trait-like. Further research may need to focus on these stable components.
Published online: 27 September 2017
Gesehen am 26.06.2018